PENGENALAN PENDIDIKAN TINGGI VOKASI DAN SOSIALISASI SELEKSI PENERIMAAN MAHASISWA BARU POLITEKNIK TRIDAYA VIRTU MOROSI TAHUN 2024 BERLOKASI DI SMA/SMK DI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Badia, Bahdin Ahad; Darwis, Mardis; Putra, Fachrizal Cesar; Jalil, Abdul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This activity aimed to introduce vocational higher education and socialize the selection of new student admissions at the Tridaya Virtu Morosi Polytechnic in 2024 to high school and vocational school students in Konawe Regency, Southeast Sulawesi. The methods used were presentations, discussions, and question and answer sessions involving resource persons from the Tridaya Virtu Morosi Polytechnic and representatives from local high schools and vocational schools. The results showed an increase in prospective students' understanding of vocational education and study opportunities at the Tridaya Virtu Morosi Polytechnic. Students' interest and enthusiasm to continue their education at the vocational level and enroll at the Tridaya Virtu Morosi Polytechnic increased after participating in this activity. This activity also helped promote the study programs offered and attract potential new students from high schools and vocational schools in Konawe Regency.